2018
DOI: 10.5194/acp-18-5765-2018
|View full text |Cite
|
Sign up to set email alerts
|

The influence of model spatial resolution on simulated ozone and fine particulate matter for Europe: implications for health impact assessments

Abstract: Abstract. We examine the impact of model horizontal resolution on simulated concentrations of surface ozone (O 3 ) and particulate matter less than 2.5 µm in diameter (PM 2.5 ), and the associated health impacts over Europe, using the HadGEM3-UKCA chemistry-climate model to simulate pollutant concentrations at a coarse (∼ 140 km) and a finer (∼ 50 km) resolution. The attributable fraction (AF) of total mortality due to long-term exposure to warm season daily maximum 8 h running mean (MDA8) O 3 and annual-avera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 43 publications
2
26
0
Order By: Relevance
“…In contrast to other studies, Thompson et al (2014) evaluated health impacts using 4-, 12-, and 36-km resolutions and came to a conclusion that mortality attributable to PM 2.5 exposure is not sensitive to resolution when uncertainties are considered. A possible reason for this may be that the range of resolutions was relatively small compared with other studies (Fenech et al 2018).…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…In contrast to other studies, Thompson et al (2014) evaluated health impacts using 4-, 12-, and 36-km resolutions and came to a conclusion that mortality attributable to PM 2.5 exposure is not sensitive to resolution when uncertainties are considered. A possible reason for this may be that the range of resolutions was relatively small compared with other studies (Fenech et al 2018).…”
Section: Introductionmentioning
confidence: 81%
“…Mortality attributable to PM 2.5 got smaller as resolution got coarser. Fenech et al (2018) used concentrations modelled with HadGEM3-UKCA chemistry-climate model at ca.140-km and ca.50-km resolutions to study health impacts of PM 2.5 in Europe and found that total mortality estimates are sensitive to a model resolution by up to ± 5% across Europe. Li et al (2016) used both air quality modelled (GEOS-Chem) and regridded concentrations at various resolutions (0.5 × 0.66°, 1 × 1.25°, 2 × 2.5°, and 4 × 5°) to estimate health impacts over the USA.…”
Section: Introductionmentioning
confidence: 99%
“…We did not perform dedicated perturbation simulations on CH 4 as an O 3 precursor, but we implemented TM5 results obtained in the frame of the first phase of the Hemispheric Transport of Air Pollutants (HTAP1) assessment Fiore et al, 2008). In one of the prescribed experiment set-ups, models evaluated how surface ozone levels respond when the global steady-state CH 4 concentration decreases by 20 % from 1760 ppbv (the global mean CH 4 concentration in the year 2000) to 1408 ppbv.…”
Section: Air Pollutant Sr Relationsmentioning
confidence: 99%
“…As shown in Table 1, two major aspects were modified in the set of five configurations: the meteorological input data and the vertical structure of the model. We fed LOTOS-EUROS with operational data from the reanalysis of the European Centre for Medium-Range Weather Forecast (ECMWF) model (Flemming et al, 2009) retrieved with a spatial resolution of 7 km × 7 km. A second meteorological gridded dataset was obtained with the Weather Research and Forecasting Model (WRF; Skamarock et al, 2008) with a resolution of 1 km × 1 km over a square domain of side 220 km centred on the city of Madrid (Fig.…”
Section: Model Experimental Designmentioning
confidence: 99%